Studies on Mycoflora Affecting Pinus gerardiana (Chilgoza) Seeds and their Management - Bhardwaj, L. N.; Gupta, V. K. (Indian Forester, 1998)
Ten fungi were found deteriorating the edible nuts of Pinus gerardiana (Chilgoza) of which Penicillium citrinum and Trichothecium roseum were the most predominant. Maximum spoilage (12 to 14%) in storage was however recorded on seeds stored in polythene bags, plastic containers and glass bottles, whereas seed stored in cloth bags, gunny bags, wooden boxes and cardboard boxes remained free from visible moldy growth even after nine months of storage where only 2 to 5% seed showed moldy growth. Out of seven fungicides tested, seeds treated with carbendazim (Bavistin, 0.05%), thiophenate methyl (Topsin, 0.05%) and benomyl (Benlate, 0.05%) provided significantly better control of P. citrinum when stored in cloth bags for nine months. However, insignificant results were obtained when seeds after fungicide treatment were stored in polythene bags.